Cerebral Dominance in Multilinguals - Kumar PJ; Nataraja NP; Subrahmanyaiah MG (Journal of All India Institute of Speech and Hearing, 1970)
The present  study  was  an  attempt  to  find  out  the  relationship  between the familiarity  of language  and  the  hemisphere  involved in processing  it, A dichotic listening task was   administered  to 10 adult  males. All of them  had Kannada  as  mother  tongue  and were familiar  with English and as  well  as  Hindi. The  results  indicate  that  the  most familiar  language seems  to  be  processed  in the  left  hemisphere